Exposure to chorioamnionitis alters the monocyte transcriptional response to the neonatal pathogen Staphylococcus epidermidis. Issue 8 (23rd April 2018) - de Jong, Emma; Hancock, David G; Wells, Christine; Richmond, Peter; Simmer, Karen; Burgner, David; Strunk, Tobias; Currie, Andrew J
Abstract: Preterm infants are uniquely susceptible to late‐onset sepsis that is frequently caused by the skin commensal Staphylococcus epidermidis . Innate immune responses, particularly from monocytes, are a key protective mechanism. Impaired cytokine production by preterm infant monocytes is well described, but few studies have comprehensively assessed the corresponding monocyte transcriptional response. Innate immune responses in preterm infants may be modulated by inflammation such as prenatal exposure to histologic chorioamnionitis which complicates 40–70% of preterm pregnancies. Chorioamnionitis alters the risk of late‐onset sepsis, but its effect on monocyte function is largely unknown. Here, we aimed to determine the impact of exposure to chorioamnionitis on the proportions and phenotype of cord blood monocytes using flow cytometry, as well as their transcriptional response to live S. epidermidis . RNA‐seq was performed on purified cord blood monocytes from very preterm infants (<32 weeks gestation, with and without chorioamnionitis‐exposure) and term infants (37–40 weeks), pre‐ and postchallenge with live S. epidermidis . Preterm monocytes from infants without chorioamnionitis‐exposure did not exhibit an intrinsically deficient transcriptional response to S. epidermidis compared to term infants. In contrast, chorioamnionitis‐exposure was associated with hypo‐responsive transcriptional phenotype regarding a subset of genes involved in antigen presentation and adaptive immunity. Overall, our findings suggest that prenatal exposure to inflammation may alter the risk of sepsis in preterm infants partly by modulation of monocyte responses to pathogens. Abstract : Preterm infants are susceptible to sepsis due to Staphylococcus epidermidis ; however, preterm infants exposed to histologic chorioamnionitis exhibit an altered risk of infection. We investigated transcriptional responses of cord blood monocytes (as key effector cells of innate immunity) following challenge with live S. epidermidis . Term and preterm infants without exposure to chorioamnionitis displayed comparable transcriptional responses, whereas exposure to chorioamnionitis was associated with a hypo‐responsive phenotype involving key immune genes. See also: News and Commentary byBermick & Schaller